INTERACTIVE AND ACTIVE TECHNOLOGIES IN TEACHING THE DISCIPLINE “MACROECONOMICS” IN HIGHER EDUCATION - I. B. Rodina; A. F. Vladimirova (Вестник университета, 2020)
The features and problems of using interactive, active and distance educational technologies in the process of teaching the educational discipline «Macroeconomics» in the preparation of bachelors in higher educational institutions of economic and managerial profile have been analysed. It has been proved, that the above-mentioned educational technologies, while being an urgent necessity and a mandatory requirement of the educational process in the digital age, include various types of breakthrough technologies in modern interdisciplinary scientific research, higher education, economic sciences. It has been substantiated, that these educational technologies are a chance for higher education in the Russian Federation to take a leading position in the world ranking of educational institutions in the context of the country’s membership in the World Trade Organization. The author’s technique of innovative teaching methods in the discipline «Macroeconomics» in the oldest Russian higher education institution has been presented.